1133. Qualitative Analysis of Pharmacists' Therapeutic Reasoning Processes Applied to Antimicrobial Selection and Stewardship Activities. (31st December 2020) - Gruenberg, Katherine; Abdoler, Emily; OBrien, Bridget C; Schwartz, Brian; MacDougall, Conan
Abstract: Background: Relative to the study of diagnostic reasoning, less is known about how clinicians make therapeutic decisions. Past work has explored how physicians choose particular antimicrobials in specific cases (antimicrobial therapeutic reasoning - ATR), but how pharmacists make similar determinations has remained unexplored. Understanding ATR by pharmacists could inform pharmacist education and improve antimicrobial stewardship (AS). Methods: We conducted individual interviews with a purposeful sample of 11 pharmacists (5 ID specialist pharmacists and 6 non-specialists), adapting a protocol for semi-structured interviews utilizing clinical vignettes based on a prior study in physicians. In addition, participants were asked to describe their ATR process generally using a novel notecard exercise. Interviews were transcribed and analyzed with Dedoose, using the prior study's codebook as an initial framework and adding and adapting codes through an iterative process. Results: We found that pharmacists generally engage in the same major ATR steps (Naming the Syndrome, Delineating Pathogens, Selecting the Antimicrobial) previously described in physicians (Figure 1). Pharmacists also seemed to incorporate similar patient- and system-factors and to utilize "therapy scripts". However, specific factors and therapy script categories did not overlap completely, with some new factors and nuances emerging (Table 1). Overall, the antimicrobial reasoning framework described for physicians encompassed pharmacists' AR, but some pharmacists described "Revisiting the Syndrome" in light of the clinical data and in some cases pharmacists appeared to filter script options (for example, due to allergies) before proceeding. Figure 1 - Antimicrobial Therapeutic Reasoning Framework Table 1 - Factors Involved in Pharmacists' Antimicrobial Reasoning Process Conclusion: The framework describing pharmacist antimicrobial ATR and is similar to that in a prior study of physicians, with some nuances that may be attributable to the pharmacist's reviewer role in AS. Application of this framework has potential to aid in teaching learners, identifying where error or bias may occur, improving multidisciplinary AS efforts, and providing a common framework for communication. Disclosures: All Authors : No reported disclosures